2011
DOI: 10.1249/mss.0b013e31820ce174
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Wearable Monitors for Assessing Sedentary Behavior

Abstract: The AP was more precise and more sensitive to reductions in sitting time than the AG, and thus, studies designed to assess SB should consider using the AP. When the AG monitor is used, 150 counts per minute may be the most appropriate cut point to define SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
730
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(762 citation statements)
references
References 22 publications
27
730
3
2
Order By: Relevance
“…One limitation inherent in the use of a hip-mounted accelerometer, such as the ActiGraph, is that its inability to discern sitting from standing still may lead to measurement error in the estimate of time spent in SB. Kozey-Keadle et al found the ActiGraph accelerometer to significantly underestimate sitting time compared with both direct observation [31] and the activPAL [32], a thigh-worn accelerometer that can detect changes in posture; however, the differences were less than 5%. Future studies should aim to verify our findings using similar devices that can differentiate between sitting and standing with higher accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation inherent in the use of a hip-mounted accelerometer, such as the ActiGraph, is that its inability to discern sitting from standing still may lead to measurement error in the estimate of time spent in SB. Kozey-Keadle et al found the ActiGraph accelerometer to significantly underestimate sitting time compared with both direct observation [31] and the activPAL [32], a thigh-worn accelerometer that can detect changes in posture; however, the differences were less than 5%. Future studies should aim to verify our findings using similar devices that can differentiate between sitting and standing with higher accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…As the activPAL records continuously, participants were required to fill out a logbook of hours spent at work. The activPAL has been shown to be a reliable and valid measure of sitting, standing and stepping time [14,15].…”
Section: Activpalmentioning
confidence: 99%
“…19 For the purpose of this paper, data were categorised into MVPA using established cut points and presented as average total MVPA (weekday and weekend) and MVPA at work. 15,20 MVPA was dichotomised as < or ≥ 30 minutes per day for use in the interaction analyses.…”
Section: Sitting Time and Physical Activity Measurementmentioning
confidence: 99%
“…However, they cannot distinguish between sitting and standing still. [13][14][15] In order to report accurately on the relationship between occupational sitting patterns and health outcomes, objective measures that measure postural change are needed.…”
Section: Introductionmentioning
confidence: 99%